The Mechanism Of The Criminal Justice System In Indonesia Towards Women's Legal Protection - Togap Silalahi; Junifer Dame Panjaitan (International Journal of Social Research, 2023)
The reseach discusses the pervasive issue of sexual violence against women, particularly within the context of domestic and sexual violence. The challenges faced by victims are multifaceted, encompassing psychological conditions, dependence on perpetrators, lack of support from family and society, patriarchal stigma, biased law enforcement, and a deficient legal and social protection system. The hierarchical relationship between victims and perpetrators is deeply rooted in patriarchal social constructions, further exacerbated by discriminatory policies, such as those found in marriage laws. The research emphasizes the economic dependence of victims and societal stigmatization of women's sexuality, attributing blame to victims rather than perpetrators. Existing legal frameworks, exemplified by the Criminal Code, are deemed inadequate and necessitate reform to address various forms of violence against women. The study employs normative legal research methods, utilizing statutory and conceptual approaches, document studies, and observations. Results indicate that the criminal justice system, while having dual functions of crime containment and secondary prevention, often becomes a criminogenous factor. The discussion underscores the need for a more comprehensive and gender-sensitive legal system, drawing attention to international legal instruments and domestic regulations aimed at protecting women's rights and ensuring justice. In conclusion, the abstract advocates for a legal system that integrates gender perspectives and emphasizes the importance of an interdisciplinary approach to maximize protection against violence targeting women.